Assessment of chemical quality of groundwater in coastal volcano-sedimentary aquifer of Djibouti, Horn of Africa. (July 2017) - Ahmed, Abdoulkader Houssein; Rayaleh, Waiss Elmi; Zghibi, Adel; Ouddane, Baghdad
Abstract: This research is conducted to evaluate the current status of hydrogeochemical contaminants and their sources in groundwater in the volcano-sedimentary aquifer of Djibouti. Groundwater samples were mostly collected from the volcanic and inferoflux aquifers and then were analyzed for quality on physicochemical parameters (EC, pH, Temperature, Cl −, SO4 2−, HCO3 −, NO3 −, Na +, Ca 2+, Mg 2+, K +, Br −, F − ), minor and trace elements (Li, Ba, B, Sr, Si, Al, Cr, Fe, Mn, Mo, Pb, Co, Cu, Ni, Zn, Ti, V, As, Se). The interpretations of hydrochemical data are shown numerically and graphically through the Piper diagram such as the multivariate statistical analysis, binary diagram, the calculation of the saturation indexes, the index of base exchanges and ratio of Na + /Cl −, SO4 2− /Cl −, HCO3 − /Cl − . The seawater ratio and ionic deviation in the groundwater were calculated using the chloride concentration. These processes can be used as indicators of seawater intrusion progress. This study reveals three groundwater quality groups and how the quality of water supply has been deteriorated through the process of seawater intrusion. The seawater intrusion extends into the Gulf basalts aquifer that covers nearly 12% of the whole area according to some observations. Some toxic elements present in drinking water (As and Se) have already exceeded the maximum permissible in almost the entire of the Gulf basalts aquifer affected by seawater intrusion. Indeed, some correlations were found between As, Se, with electrical conductivity and among other minor and trace elements such as Br, B, Sr, Co and Cr. It indicates that all these elements are mainly controlled by naturel/geogenic processes. The Principal component Analysis and the Hierarchical Cluster Analysis have led to the confirmation of the hypotheses developed in the previous hydrochemical study in which two factors explain the major hydrochemical processes in the aquifer. These factors reveal first the existence of an intensive intrusion of seawater and second the mechanisms of contamination through the recharge processes of groundwater. Consequently, the assessment of water quality and the determination of the risk of water contamination by pollution seems to be very useful for an effective management of groundwater resources, and also for preventing salinization and minimizing the phenomena of seawater intrusion. Highlights: Aquifer of Djibouti is vulnerable to contamination by anthropological activities. Hydrogeochemical explored as a tool of protecting groundwater resources. Multivariate statistics with geochemical modeling revealed the main sources of contamination. Two factors were found that explained major hydrochemical processes in the aquifer. There are a relationship between seawater intrusion and recharge contamination.